Syringomyelia secondary to thoracic intervertebral disc protrusion: a rare condition - Hui, Soo Tze; Anas, Tharek; Ibrahim, Idris; Zakaria, Mohd Hazeman (Asian Network for Scientific Information (ANSINET), 2022)
Spinal spondylosis is an extremely common problem among the middle-aged and elderly population. However, it is an extremely rare cause of syringomyelia in clinical practice. The differentiation between syringomyelia and hydromyelia is not always straightforward and rather exhaustive. Spinal cord compression and instability are the proposed mechanisms of injury-causing syringomyelia. Symptomatic presentation depends primarily on the location of the syrinx within the neuraxis, be it motor, sensory or autonomic disturbance. There were abundant of successful cases in the past, whereby surgical interventions can regress the appearance of syringomyelia in magnetic resonance imaging. However, there was a mixed result in terms of patients' symptom. There were only 6 reported articles of syringomyelia secondary to cervical spondylosis found worldwide. We describe a case of T11/T12 thoracic intervertebral disc protrusion causing long segment syringomyelia till conus medullaris.